Diseño de un sistema de tratamiento de aguas residuales en la Planta Agroindustrial del campus Salache, Universidad Técnica de Cotopaxi - Guerrero Crespo, Maritza del Carmen (2023)
The Agroindustrial Plant of the Technical University of Cotopaxi, prepares competitive professionals and enhances the field of industrialization, combining knowledge and practice, this is how different processes are carried out with students in the production of meat, vegetables and dairy products mainly. It has a purification treatment system so that the water used meets the technical and quality requirements for the equipment used in the different processes. Once the water is used, it is discharged directly into a septic tank without prior treatment. Within the product manufacturing processes, water changes its physical-chemical and microbiological characteristics, becoming wastewater, so it is essential to think of a treatment system that complies with the permissible limits within the current legal regulations, thus creating sustainable and environmentally friendly processes. Wastewater treatment consists of a series of physical, chemical and biological processes whose purpose is to eliminate the different types of contaminants present in the effluent water, such as BOD5, COD, Oils and greases, surfactants, suspended solids, which are are out of regulation. The purpose of the proposed treatment is to condition the effluent to the best technical and economic characteristics for its return to the environment and final disposal, fulfilling and answering the research questions raised in this research work.